2021
DOI: 10.3390/cells10113196
|View full text |Cite
|
Sign up to set email alerts
|

Reactivities of a Prostanoid EP2 Agonist, Omidenepag, Are Useful for Distinguishing between 3D Spheroids of Human Orbital Fibroblasts without or with Graves’ Orbitopathy

Abstract: Background. To obtain new insights into the activation of the thyroid-stimulating hormone (TSH) and insulin-like growth factor 1 (IGF-1) receptors in human orbital fibroblasts (n-HOFs), the effects of the prostanoid EP2 agonist, omidenepag (OMD), and a rho-associated coiled-coil-containing protein kinase (ROCK) inhibitor, ripasudil (Rip) were evaluated using three-dimension (3D) n-HOFs spheroids in the absence and presence of the recombinant human TSH receptor antibodies, M22 and IGF-1. Methods. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…To support this hypothesis, a previous study demonstrated that flightless-I (FLII), a transcriptional modulator of PPARγ, binds directly to PPARγ through the LRR domain and suppresses the transcriptional activity of cells [ 69 ]. Furthermore, in addition to the current observations related to the Seahorse real-time cellular metabolic analyses of n-HOFs and GHOFs ( Supplemental Figure S2 ), we previously reported that a significant difference existed between GHOFs and n-HOFs that had been treated with M22 and IGF1 in terms of mRNA expression levels of several molecules including ECM molecules (COL1, 4 and 6 and FN), ECM regulatory factors (LOX and CTGF), inflammatory cytokines (IL1B and IL6) and ER stress-related factors, suggesting the presence of some additional, unrelated TSHR effects by M22 and IGF1 [ 30 ]. However, this TSHR-independent cross-reactivity by M22 and IGF1 is speculative at this time, and additional studies such as a TSHR knockdown system and others will be required to reveal the magnitude of this issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To support this hypothesis, a previous study demonstrated that flightless-I (FLII), a transcriptional modulator of PPARγ, binds directly to PPARγ through the LRR domain and suppresses the transcriptional activity of cells [ 69 ]. Furthermore, in addition to the current observations related to the Seahorse real-time cellular metabolic analyses of n-HOFs and GHOFs ( Supplemental Figure S2 ), we previously reported that a significant difference existed between GHOFs and n-HOFs that had been treated with M22 and IGF1 in terms of mRNA expression levels of several molecules including ECM molecules (COL1, 4 and 6 and FN), ECM regulatory factors (LOX and CTGF), inflammatory cytokines (IL1B and IL6) and ER stress-related factors, suggesting the presence of some additional, unrelated TSHR effects by M22 and IGF1 [ 30 ]. However, this TSHR-independent cross-reactivity by M22 and IGF1 is speculative at this time, and additional studies such as a TSHR knockdown system and others will be required to reveal the magnitude of this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence or absence of 100 ng/mL IGF1 and/or 10 ng/mL M22, two-dimensional (2D) planar and three-dimensional (3D) spheroid cultures of 3T3-L1 preadipocytes (#EC86052701-G0, KAK) were maintained for 7 days [ 24 , 25 ], or n-HOFs [ 30 , 70 , 71 ] or GHOFs [ 29 , 72 ] were maintained for 10 days, as described previously. The induction of adipogenic differentiation of the 3T3-L1 cells was also carried out as described previously [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various in vitro 3D cell culture methods, a simpler model, a 3D spheroid culture model, has been the most widely used [28,29]. In our recent investigations, to characterize the microenvironments of various tissues, we independently developed unique 3D drop cell culture methods using several non-cancerous cells including human conjunctival fibroblasts (HconF) [30], human orbital fibroblasts (HOF) [31], human scleral stromal fibroblasts (HSclF) [32] and human scleral fibroblasts (HSSF) [33], and Graves'-diseaserelated HOF (GOF) [34], as well as cancerous cells including an A549 lung adenocarcinoma cell line [35], various malignant melanoma (MM) cell lines [36] and various OSCC. As expected, our findings indicated that the biological natures of the 3D spheroid models were markedly different and distinct from those of 2D cultured models even though both were prepared under exactly identical experimental conditions except that the culture plates that were used were different [37].…”
Section: Introductionmentioning
confidence: 99%